3 - We Decide, They Decide For Us: Popular Participation as an Issue in Two Nigerian Women’s Development Programmes: par Emma T. Lucas - Lucas, Emma T. (Africa Development, 2001)
Participation at all levels of organizing, programme development, and implementation is critical if development programmes are to meet a minimum level of success. An examination of the organizational decision-making structure of two Nigerian women's development organizations, Better Life for Rural Women (BLP), a government-sponsored programme, and Country Women's Association of Nigeria (COWAN), a non-governmental programme, reveals fundamental differences in the level of participation of rural women who were the intended beneficiaries. The mission of each focused on the improvement of rural women's lives; however, the success of the non-governmental organization far outweighed the government- sponsored one because of its basic belief in popular participation. BLP was more likely to encourage bureaucratic and individual politically motivated manoeuvres that only delayed and sometimes subverted altogether services that were specifically designed for rural women. COWAN was less likely to experience these barriers, and therefore more readily responded to and engaged rural women as full participants in development projects that focused on improving their lives. Because of political instability, government projects focusing on women are limited. However, their need for development programmes that directly address their concerns is as great as ever.